Det transnationella ansvaret - En kvalitativ studie om kosovoalbanska migranters försörjningsansvar av familjemedlemmar i Kosovo - Tahiri,Vlora (2013)
Abstract Author: Vlora Dibrani Title: The transnational responsibility - A qualitative study about Kosovoalbanian migrants supply responsibilities of their family members in Kosovo Supervisor: Anders P. Lundberg Keywords: Family, Kosovo, migrants, remittances, transnational The aim of this study was to investigate the expectations the Kosovoalbanian social system has on the migrants supply responsibilities against their family members in Kosovo, and how the Kosovoalbanian migrants in Sweden handle their responsibilities in the intersection between a Kosovoalbanian and a Swedish social system. To achieve my purpose, I conducted qualitative interviews with three kosovoalbanian migrants in Sweden, which still have some connection with relatives in Kosovo. I also interviewed three social workers in the social service in Kosovo. I used the theoretical concepts; transnationalism and migration. The results of the survey showed that migrants have a certain obligation to supply their family members who still lives in Kosovo. The main responsibility lies on the men who migrated and according to the social workers, the migrants have a supply obligation to support parents, but not an equal responsibility to supply their siblings or other relatives. The study also showed that the migrants in the investigation are involved in the transnational process by providing financial assistance to families in Kosovo, based on their circumstances and according to the needs that exist.
Keywords: Familj; Kosovo; Migranter; Remitteringar; Transnational